2018
DOI: 10.1017/s1755691018000646
|View full text |Cite
|
Sign up to set email alerts
|

Distributions and risks of Cu, Cd, Pb and Zn in soils and rice in the North River Basin, South China

Abstract: As the largest industrial and population centre in China, the Pearl River Delta is facing a growing threat of heavy metal pollution from local mining and power industries. This study investigates the distribution and potential health risks of copper (Cu), cadmium (Cd), lead (Pb) and zinc (Zn) in paddy soils and rice at four typical sites. The Nemerow synthetic pollution index (PN) of soils from Fogang, Dabao Mountain, Shaoguan and Lechang were 8.40, 9.10, 4.64 and 10.28, respectively, indicating serious pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Lange et al reported that the Zn content was one of the main variables that allowed to discriminate the rice origin of samples from Brazil; in their work, samples were taken from a nearby geographical zone to Uruguayan rice crops, and our results were in accordance with their results [22]. Despite the dependence of the trace element composition and the geographical zone, reported ranges of Cu and Zn levels are wide, and these results were also in good agreement with those found in polished rice from China (mean value for Cu: 2.7 mg kg −1 and 20.9 mg kg −1 for Zn) [1,3,23]. e sample "brand C" was parboiled; there was no declaration of fortification in the label.…”
Section: Analysis Of Rice Samplessupporting
confidence: 89%
See 1 more Smart Citation
“…Lange et al reported that the Zn content was one of the main variables that allowed to discriminate the rice origin of samples from Brazil; in their work, samples were taken from a nearby geographical zone to Uruguayan rice crops, and our results were in accordance with their results [22]. Despite the dependence of the trace element composition and the geographical zone, reported ranges of Cu and Zn levels are wide, and these results were also in good agreement with those found in polished rice from China (mean value for Cu: 2.7 mg kg −1 and 20.9 mg kg −1 for Zn) [1,3,23]. e sample "brand C" was parboiled; there was no declaration of fortification in the label.…”
Section: Analysis Of Rice Samplessupporting
confidence: 89%
“…e determination of the micronutrient content such as copper (Cu) and zinc (Zn) in different types of rice is not only important to know about its nutritional value but also to characterize the cereal from the point of view of other characteristics such as its genotype [1]. ese elements are also of interest to monitor anthropogenic activities that can generate contamination in food [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…XKS mine covers 70 km 2 and is located in Loudi city, the central part of Hunan Province, China. It lies between 27 • 30 49"-27 • 50 38" S latitude and 111.18 57"-111.…”
Section: Xks Areamentioning
confidence: 99%
“…Potentially Toxic Elements (PTEs) are considered as toxic and persistent pollutants in soil which remain in local ecosystems for a long time and pose a negative threat to human health [1,2]. When PTEs in soil are transformed from solid to ionic form and methylated, they will accumulate in organisms, threatening the safety of animals and humans through the food chain [3].…”
Section: Introductionmentioning
confidence: 99%
“…The large-scale land destruction caused by mining is a serious and increasingly valued problem in China and the world [1,2]. Open pit mining directly destroys the surface soil layer and vegetation, and underground mining leads to surface collapse, resulting in the destruction of land and vegetation.…”
Section: Introductionmentioning
confidence: 99%